Museums and the working class - Chynoweth, Adele (Abingdon, Oxon ; New York, NY : Routledge, 2022)
"Museums and the Working Class is the first book to take an intersectional and international approach to the issues of economic diversity and class within the field of museum studies. Bringing together 16 contributors from eight countries, this book has emerged from the significant global dialogue concerning museums' obligation to be inclusive, participate in meaningful engagement and advocate for social change. As part of the push for museums to be more accessible and inclusive, museums have been challenged to critically examine their power relationships and how these are played out in what they collect, whose stories they exhibit and who is made to feel welcome in their halls. This volume will further this professional and academic debate through the discussion of class. Contributions to the book will also reinforce the importance of the working class - not only in collection and exhibition policy, but also for the organisational psychology of institutions. Museums and the Working Class is essential reading for scholars and students of museum, gallery and heritage studies, cultural studies, sociology, labour studies and history. It will also serve as a source of honest and research-led inspiration to practitioners working in museums, galleries, libraries, archives and at heritage sites around the world"--
OCLC-licensed vendor bibliographic record.
Keywords: Museums -- Social aspects; Working class -- Historiography; Labor -- Historiography; Museums -- Collection management; Cultural property -- Protection; SOCIAL SCIENCE / Social Classes; BUSINESS & ECONOMICS / Labor